Topo4qgis-un plugin per QGIS utile all’elaborazione di libretti PreGeo e alla trattazione di liste di punti mediante opportuna rototraslazione ai minimi quadrati - Beccaria, Gianluca; Lombardi, Marco (GEOmedia, 2022)
topog4qgis is a QGis 3 plugin for the italian cadastre update procedure (PreGeo) that allowing the user to manage classical surveys and gps or points list (.csv files). Least mean square method georeferencing the survey in an absolute official geographic space is allowed by measuring, during surveys, the trigonometrical points and by using the official map from the cadastre database (.edm files) or by reading the trigonometricals table (.taf files). Surveying of delimiting lines (e.g. between particles, or delimiting a building) is correctly interpreted by the plugin. Please note that this plugin is mainly related to datas provided by the italian surveying agency (former Agenzia del Territorio is now Agenzia delle Entrate), and its use is then strictly limited to the italian country but use of points lists (.csv files) allows to use for other country with the same cadastre cartografy system.